A Study of Community Perceptions in Jember about Islamic Banking and the Reasons People Do Not Choose Sharia Banks - Yani Dahliani (International Journal of Economics, Commerce, and Management, 2025)
This study aims to uncover public perception of Islamic banking in Jember Regency as well as the factors that cause low account ownership in Islamic banks, even though the majority of the population is Sunni Muslim. This study uses a descriptive qualitative approach with data collection techniques through direct interviews with people who do not choose Islamic banks as financial institutions. The results of the study show that the low level of public knowledge about Islamic banking systems and products is the main factor influencing their decisions. In addition, promotions carried out by Islamic banks are considered less effective and do not directly touch the needs and understanding of the community. The lack of supporting facilities such as ATMs and service offices also strengthens the perception that Islamic banks are not significantly different from conventional banks. Weak branding and education cause Islamic banking products to be less attractive in the eyes of the public. Therefore, a more intensive education strategy and a promotional approach that directly touches the community, as well as an improvement of basic service facilities so that Islamic banks can provide optimal services and increase public trust. This study recommends strengthening Islamic financial literacy and expanding access to services as strategic steps to encourage Islamic financial inclusion in Jember.